A practical guide to English pronunciation : a self-study or classroom course in British English pronunciation - SUCIU, Giulia (Presa Universitară Clujeană, 2026)
The book is designed for self-study or classroom use, introducing you to the sounds and symbols of the standard British English Pronunciation, also known as General British or GB English.